Pinna reconstruction in a 2-year-old: a case report - Gupta, Pallavi; Gupta, Piyush; Randhawa, J. S. (International Journal of Research in Medical Sciences, 2024)
Pediatric age group is one of the most vulnerable groups to trauma and morbidity occurring thereby. And that too requiring reconstruction of ear pinna is in itself a challenge. Confronted with such situation is not an easy situation for any trauma team. Successful outcomes in auricular reconstruction rely on the surgeon’s careful analysis of the defect as well as knowledge of the different reconstructive options available. We present one such case and discuss the relevant anatomy and operative options for surgeons.